Early Christianity’s Polemical views of Jews and Judaism: a Sociological Perspective - Lightstone, Jack N. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1987)
Early Christians had no single, shared perception of Jews and of Judaism. For some, Jews are demonic, while for others, they provide access to heaven’s blessings. It appears difficult to account for such variation in theological terms alone. Rather, distinctive social patterns extant in Late Antique Christianity better explain either the abhorrence of, or fascination with, Jews and Judaic rites. One such social pattern characterizes emergent Roman orthodoxy. Another reflects an earlier, more decentralized Christianity which persisted alongside the former well into the late 4th century, if not beyond. For each type of Christian community the characterization of jews is shown to “fit” the group’s “mapping” (1) of the loci of the sacred and (2) of social order and authority. These congruences help render each mapping cogent—and with them, the perceptions of Jews and Judaism.